Differential expression of systemic inflammatory mediators in amputees with chronic residual limb pain. Issue 1 (23rd September 2016) - Chamessian, Alexander; Van de Ven, Thomas; Buchheit, Thomas; Hsia, Hung-Lun; McDuffie, Mary; Gamazon, Eric R.; Walsh, Colin; Bruehl, Stephen; Buckenmaier, Chester 'Trip'; Shaw, Andrew
Abstract : Traumatic amputees with residual limb pain have a significant increase in proinflammatory markers that correlates positively with pain intensity and pain catastrophizing. Abstract: Chronic postsurgical pain impacts most amputees, with more than half experiencing neuralgic residual limb pain. The transition from normal acute postamputation pain to chronic residual limb pain likely involves both peripheral and central inflammatory mechanisms. As part of the Veterans Integrated Pain Evaluation Research study, we investigated links between systemic inflammatory mediator levels and chronic residual limb pain. Subjects included 36 recent active duty military traumatic amputees with chronic residual limb pain and 40 without clinically significant pain. Blood samples were obtained and plasma concentrations of an array of inflammatory mediators were analyzed. Residual limb pain intensity and pain catastrophizing were assessed to examine associations with inflammatory mediators. Pro-inflammatory mediators including tumor necrosis factor (TNF)-α, TNF-β, interleukin (IL)-8, ICAM-1, Tie2, CRP, and SAA were elevated in patients with chronic residual limb pain. Across all patients, residual limb pain intensity was associated positively with levels of several proinflammatory mediators (IL-8, TNF-α, IL-12, TNF-β, PIGF, Tie2, SAA, and ICAM-1), and inversely with concentrations of the anti-inflammatory mediator IL-13, as well as IL-2 and Eotaxin-3. Pain catastrophizing correlated positively with IL-8, IL-12, TNF-β, PIGF, and ICAM-1, and inversely with IL-13. Significant associations between catastrophizing and residual limb pain intensity were partially mediated by TNF-α, TNF- β, SAA, and ICAM-1 levels. Results suggest that chronic postamputation residual limb pain is associated with excessive inflammatory response to injury or to inadequate resolution of the postinjury inflammatory state. Impact of pain catastrophizing on residual limb pain may be because of part to common underlying inflammatory mechanisms.